Intervenção do estilo de vida na abordagem do excesso de peso e obesidade - relevância e contributo da telemedicina - Rita Sofia Fonseca de Almeida (2022)
Objective: To analyze and synthesize the available evidence about the most effective types of lifestyle intervention in the treatment of obesity. Methods: A bibliographic review was carried out based on articles selected after searching the electronic databases Pubmed, Medline and Google Scholar. Statistical data from some websites of health and epidemiological organizations were also used. A total of 63 articles were analyzed in full. Conclusion: It was concluded that low-energy diets, regardless of the macronutrients used and whether the diet was more traditional or more innovative, using meal replacements, are the ones with the most positive and lasting results in weight loss. Aerobic training combined with resistance training, even if performed at various times throughout the day, leads to greater weight loss when compared to the benefits of the modalities practiced separately. Behavioral therapy should include self-monitoring, goal setting, stimulus control, and positive reinforcement. Although individual sessions offer specific care, group sessions are more economical, free up time for health professionals and are even considered slightly more effective. The increasing accessibility to digital media allows the treatment of obesity to be performed remotely via telemedicine, taking information to a greater number of people in a short period of time. Despite telemedicine being less effective compared to face-to-face treatment, it has several advantages: the wide range of interventions and a better cost-effectiveness. Available studies were carried out in ideal environments. Treatment in these circumstances proves to be effective, so it is necessary to expand these methods in a variety of environments, emphasizing the use of telemedicine to impact public health, improving it. Weight loss is important but maintaining that loss throughout life becomes central to the fight against obesity and mitigation of consequences.